Hydrogen peroxide release and hydroxyl radical formation in mixtures containing mineral fibres and human neutrophils. Issue 11 (November 1992) - Leanderson, P; Tagesson, C
Abstract : The ability of different mineral fibres (rock wool, glass wool, ceramic fibres, chrysotile A, chrysotile B, amosite, crocidolite, antophyllite, erionite, and wollastonite) to stimulate hydrogen peroxide (H2O2) and hydroxyl radical (OH.) formation in mixtures containing human polymorphonuclear leucocytes (PMNLs) was investigated. In the presence of azide, all the fibres caused considerable H2O2 formation, and about twice as much H2O2 was found in mixtures with the natural fibres (asbestos, erionite, and wollastonite) than in mixtures with the manmade fibres (rock wool, glass wool, and ceramic fibres). In the presence of externally added iron, all the fibres were found to generate OH. and the natural fibres caused about three times more OH. formation than the manmade fibres. In the absence of external iron, there was less OH. formation; however, amosite, crocidolite, antophyllite, erionite, and wollastonite still generated considerable amounts of OH., also under circumstances in which only small amounts of OH. were produced in mixtures with the manmade fibres. These findings indicate that natural fibres generate more H2O2 and OH. than manmade fibres when incubated with PMNLs in the presence of external iron. They also suggest that the natural fibres, amosite, crocidolite, antophyllite, erionite, and wollastonite may act catalytically in the dissociation of H2O2 to OH. in the absence of external iron, whereas manmade fibres such as rock wool, glass wool, and ceramic fibres, do not seem to be able to generate OH. in the absence of external iron.